1972
DOI: 10.1111/j.2042-3306.1972.tb03887.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Impaction in a Pony: Relief via Laparotomy

Abstract: SUMMARY A case of gastric impaction in an 11 year old pony which was successfully treated by a gastrotomy is described. RÉSUMÉ On rapporte un cas de surcharge gastrique chez un poney de 11 ans guéri par gastrotomie. ZUSAMMENFASSUNG Der Artikel beschreibt einen Fall von Magenüberladung bei einem Pony, der erfolgreich durch Gastrotomie behandelt wurde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
1

Year Published

1974
1974
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…In addition, the median duration of symptoms was 3 days. In contrast, previous reports suggested that the condition is associated with severe pain (Jones et al . 1972; Barclay et al .…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In addition, the median duration of symptoms was 3 days. In contrast, previous reports suggested that the condition is associated with severe pain (Jones et al . 1972; Barclay et al .…”
Section: Discussioncontrasting
confidence: 58%
“…Enteral fluid therapy was shown to be of value in treating gastric impactions in this study. The majority of previous reports on successful treatment have focused on surgical intervention (Jones et al . 1972; Barclay et al .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the severity, chronicity, advanced stage of debilitation and lack of response to initial treatment, an unfavourable long term prognosis was given to these patients, and euthanasia recommended and elected by the owners. However, it must be acknowledged that reports of successful surgical management of the condition can be found in the veterinary literature, with success apparently depending on the primary cause of the dilatation (Jones et al 1972, Owen et al 1987, Parker et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…1987). Possible causes of primary gastric impaction include feed stuffs that swell or form a mass after ingestion (persimmon seeds, mesquite beans, wheat, barley and sugar beet pulp), dental disease, inadequate water supply, rapid food intake and pathophysiological disturbances such as abnormal gastric motility or secretion (Jones et al . 1972; Honnas and Schumacher 1985; Owen et al .…”
mentioning
confidence: 99%
“…2011). However, some horses can have a more acute and severe clinical presentation (Jones et al . 1972; Barclay et al .…”
mentioning
confidence: 99%